P59 Health inequalities in infectious diseases: a rapid review of reviews. (26th August 2022) - Ayorinde, Abimbola; Ghosh, Iman; Ali, Ifra; Zahair, Iram; Olarewaju, Olajumoke; Singh, Megha; Meehan, Edward; Anjorin, Seun; Rotheram, Suzanne; Barr, Benjamin
Abstract : Background: There are significant inequalities in various infectious disease issues. This includes the exposure, prevalence and consequences of various vaccine preventable infectious diseases, access to/utilisation of vaccines as well as antimicrobial resistance (AMR). We conducted a rapid review of reviews to synthesise existing literature on inequalities in infectious disease based on three dimensions of inequalities; inclusion health groups, protected characteristics, and socioeconomic inequalities. Methods: We searched Medline, Embase, Web of Science, and Open Grey databases in November 2021 and contacted experts. Reviews published in any language from the year 2000 were eligible provided they examined inequalities in the incidence, prevalence or consequences of infectious diseases, AMR or vaccination uptake. We excluded reviews which excluded the United Kingdom (UK) in their eligibility criteria, such as those that focus solely on low- and middle-income countries, to ensure that the findings are relevant to the UK setting. Although our search strategy focused on tuberculosis, human immunodeficiency virus, sexually transmitted infections, Hepatitis C, vaccination, and AMR, eligible reviews of any other infectious diseases were also included. One reviewer screened all the titles and abstracts, a second reviewer double screened a random sample and potentially eligible full texts were screened independently by two reviewers. We extracted relevant data using a pre-piloted form and used the Assessment of Multiple Systematic Reviews version 2 (AMSTAR2) checklist to appraise the quality of included reviews. We created an evidence matrix on Microsoft Excel showing which reviews reported on different dimensions of inequalities and for which infectious diseases. We presented this visually using heat maps. We synthesised the evidence descriptively using the dimension of inequalities. Results: After screening 11135 citations and 437 full text articles, we included 108 reviews. The included reviews covered all the dimensions of inequalities for most of the infectious disease topics of interest. However, the quality and volume of review evidence varied across all the dimensions of inequalities examined. The existing reviews provide strong evidence that people of inclusion health groups and lower socio-economic status are consistently at higher risk of infectious diseases, AMR, and incomplete/delayed vaccination. Ethnicity and sexual orientation also contribute substantially to inequalities across the various infectious disease topics we examined. Conclusion: While policy makers often focus on specific infectious diseases separately, this review of reviews provides evidence that developing targeted interventions for high-risk groups rather than individual infectious disease might be a more efficient approach to mitigating health inequalities in infectious diseases.